O impacto da crença no mundo justo e da vitimização secundária nas decisões de justiça para vítimas e perpetradores em casos de violência sexual - Tavares, Suiane Magalhães (2025)
According to the literature on people's reactions to situations of injustice, people's commitment to the pursuit of justice is a principle that guides their reaction when they are faced with such sinations. Peopic are motivated to repair injustice by compensating the victim for their suffering and punishing those responsible for the situation of injustice, respectively called behaviors that promote "restorative justice" and "retributive justice". For example, in situations of violence, people tend to act in a way that compensates the victim and punishes the aggressor, However, this equation is not linear, as people's reactions to these situations depend on the meaning of belonging and the social value of victims and aggressons, Specifically, in the violence experienced by women in relationships between intimate partners, which is omnipresem in the history of human relationships, the attribution of responsibility for their own misfortune to the victim stands out. This phenomenon is called secondary victimization and manifests ibell in several ways, inchoding blaming the victim, minimizing her suffering and avoiding comact with the victim of violence to deny het the social support necessary to repair the injustice of which she is a victim and omitting punishment of aggressors. Within the framework of this dynamic, a critical question yet to he answered is whether, paradosically, people's motivation to do justice is related to less reparation for the victim for their suffering and the acquittal of the aggressor in a context of extreme sexual violener, such as in rape situations, Furthermore, to date, the literature on this issue has given little attention to how people respond to compensating and punishing both the victim and the perpetrator samudraneously. In this scenario, based on the Just World Belief Theory (BFW), which postulates that people are motivuted to act as if they believe that the world is a fair place, wiure everyone gets what they deserve and deserves what they get, this thesis proposes the hypothesis that HIW favors people to judge the situation by promoting secondary victimization, forming a paychosociological process that can explain how men and women avoid compensating rape victims and tend to absorb the aggressors. To test this hypothesis, we propose a research program consisting of these articles, strucnred as folkrws: in the first article, which comists of four studies, we focus on presenting evidence of the validity of a scale that mesures individual differences regarding the secondary victimization of victims of rape: blaming, avoiding and minimizing. In Study 1, the scale items were developed, and their content sulidation was analyzed. In Staly 2, an exploratory analysis of its factorial structure was carried out and the fixation of the nems in three theoretically prodictod factors was verified. In Study 3, we confirmed this three-factor structure through confinatory analysis. In Study 4, we explored the predictive validity of the scale, proposing the hypothesis that secondary victimization medianes the effect of BJW on participants behavior toward a rape victim. The results showed that secondary victimization, especially minimization and blame, explain the relationship between BJW and the amount of compensation awarded to a victim of sexual violence, In the second article of a correlational nature, we went father by carrying out a study with perpetrators (Men 102) and victims of violence (Women-97). In this study, we tested the hypothesis that perpermators would compensate a victim less compared to participams who were victims of violence, and that this process would be sequentially melisted by BJW and secondary victimization. The results showed that the aggressors attributed less compensastino to the viutum compared to the perticipants and attributed greater compensation to the aggressor. However, only the first relationship was explained sequentially by BIW and secondary victimization. In article there, Study 1. we replicate the previous study in order to understand how individuals compensate victims and absolve perpetrators. In the third article, we conducted three experimental studies to manipulate the context following a rape situation. Study 1 (N = 227) | indicated that participants with a high Belief in a Just World penalized the victim more, reducing her compensation when the report was made to the police (instead of social media) and when it occurred one month alber the incident. Stoly 7(N = 248) * c confirmed these findings and showed that the court decsson influenced the victim's secondary victimization, especially when the perpetrator's punishment motivated participants from the same social category to blame her. Study 3 (N = 250) * z replicated the previous results and revealed thun men victimized the victim more than women. The results we obtained across the set of studies, while confinning our predictions, highlight the need for future research to deepen our understanding of how people react when a victim is compensaned, and the perpetrator is punished.